2017
DOI: 10.1515/jppr-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Russian olive witches’-broom disease and its insect vector in Northwestern Iran

Abstract: Recently, Russian olive trees showing witches'-broom and little leaf symptoms have been widely observed in northwestern and central Iran. Polymerase chain reaction (PCR) and nested PCR assays using phytoplasma universal primer pairs confirmed phytoplasma symptomatic infection of trees. Sequence analyses showed that 'Candidatus Phytoplasma asteris' was the causal agent of the disease in these regions. However, RFLP results using restriction enzymes HpaII, EcoRI, HinfI and AluI indicated that the collected isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In previous studies, the 'Ca. Phytoplasma asteris' was characterized as the causal agent of Russian olive witches 'broom disease in Iran [3,15]. However, MetaPhlAn2 analysis suggested that, in addition to 'Ca.…”
Section: Genomic Characterization Of Phytoplasmas With Russian Olive ...mentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, the 'Ca. Phytoplasma asteris' was characterized as the causal agent of Russian olive witches 'broom disease in Iran [3,15]. However, MetaPhlAn2 analysis suggested that, in addition to 'Ca.…”
Section: Genomic Characterization Of Phytoplasmas With Russian Olive ...mentioning
confidence: 99%
“…Later, the 'Ca. Phytoplasma asteris' was recognized, associated with the infected trees [3], and then the genome of Iranian 'Ca. Phytoplasma asteris' was obtained using NGS analysis [15].…”
Section: Russian Olive Witches'-broom Disease Importance In the North...mentioning
confidence: 99%
See 2 more Smart Citations